Complex decisions: correlates of injectable contraceptive discontinuation following HIV-1 seroconversion in an HIV prevention trial. Issue 6 (3rd June 2019) - Caplan, Margaret R.; Landovitz, Raphael J.; Palanee-Phillips, Thesla; Nair, Gonasagrie; Mhlanga, Felix; Balkus, Jennifer E.; Riddler, Sharon A.; Gorbach, Pamina M.
ABSTRACT: Contraceptive adherence during acute and recent HIV-1 infection is important to maternal and child health given the elevated risk of vertical HIV-1 transmission and additional complications of pregnancy. Injectable contraception (IC) is the most common non-barrier modern contraception method used in sub-Saharan Africa (SSA). Adherence to IC after HIV-1 seroconversion is not well understood. We examined factors associated with IC discontinuation among women in SSA diagnosed with HIV-1 infection while participating in a clinical trial of biomedical HIV-1 prevention. After diagnosis with HIV-1 infection in the VOICE trial, 255 women from South Africa, Uganda, and Zimbabwe enrolled in a longitudinal observational study (MTN-015). Contraceptive method was assessed at MTN-015 baseline and at 3, 12, and 24 months post-seroconversion. Correlates of IC discontinuation were examined by Cox proportional hazard modeling. IC use was reported at baseline by 78% of women enrolled (198/255), of which 92% (182/198) completed at least one follow-up visit. Two-thirds of women (66%, 121/182) continued on IC during the follow-up period (median 24 months). Lower rates of IC discontinuation were observed in women who reported having had at least one child (HR 0.39, 95% CI 0.20–0.82) or earning a personal income (HR 0.51, 95% CI 0.30–0.87) at baseline. These findings suggest that many women with HIV-1 infection face complex decision-making regarding family planning in the years that follow seroconversion and highlight that some women may discontinue IC use despite on-site provision of family planning services. Understanding the broader context of family planning choices in recently seroconverted women may be key to more effective linkages between family planning services and HIV-1 testing and care.